Future Directions for Meningitis Surveillance and Vaccine Evaluation in the Meningitis Belt of Sub-Saharan Africa. (31st October 2019) - Novak, Ryan T; Ronveaux, Olivier; Bita, André F; Aké, Honoré Flavien; Lessa, Fernanda C; Wang, Xin; Bwaka, Ado M; Fox, LeAnne M
Abstract: In sub-Saharan Africa, bacterial meningitis remains a significant public health problem, especially in the countries of the meningitis belt, where Neisseria meningitidis serogroup A historically caused large-scale epidemics. In 2014, MenAfriNet was established as a consortium of partners supporting strategic implementation of case-based meningitis surveillance to monitor meningitis epidemiology and impact of meningococcal serogroup A conjugate vaccine (MACV). MenAfriNet improved data quality through use of standardized tools, procedures, and laboratory diagnostics. MenAfriNet surveillance and study data provided evidence of ongoing MACV impact, characterized the burden of non-serogroup A meningococcal disease (including the emergence of a new epidemic clone of serogroup C), and documented the impact of pneumococcal conjugate vaccine. New vaccines and schedules have been proposed for future implementation to address the remaining burden of meningitis. To support the goals of "Defeating Meningitis by 2030, " MenAfriNet will continue to strengthen surveillance and support research and modeling to monitor the impact of these programs on meningitis burden in sub-Saharan Africa.